Upaya Meminimalisir Tingkat Cacat Proses Produksi Pada Fabrikasi Pipe Support MSP – Triraya Menggunakan Metode Fishbone Diagram Dan 5w + 1H - Sajidah Tiara Ayu Wiranda; Iriani Iriani (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Quality is an important factor in production, so companies must maintain the quality of their products in order to be able to compete in the market. One of them is PT. Swadaya Graha operates in the construction and fabrication services sector, working on several projects, one of which is pipe support. In pipe support fabrication there are problems during the production process. This problem is the presence of